Intrapelvic Migration of Cephalic Screw: Report of two Cases and Review of the Literature (London Journal of Medical and Health Research, 2025)
Intramedullary nails are widely used to treat extracapsular femoral neck fractures, providing a minimally invasive approach that allows early weight-bearing. However, in about 5% of cases, proper fixation is not achieved. One rare complication is the intrapelvic migration of the cephalic screw, which occurs in less than 0.5% of cases. This study reports two cases of intrapelvic screw migration and reviews the literature on this complication.A retrospective descriptive study was conducted at our hospital between 2015 and 2022, analyzing two cases of cephalic screw migration following hip fracture treatment. Case 1 involved an 85-year-old male who underwent treatment for a right pertrochanteric fracture with a Gamma 3 nail. Three months post-surgery, the cephalic screw migrated into the pelvic cavity, requiring removal via laparotomy. A partial hip prosthesis was implanted in a subsequent surgery, and the patient recovered successfully. Case 2 involved an 83-year-old female with multiple comorbidities. After a right pertrochanteric fracture was treated with a PFNA nail, the cephalic screw migrated intrapelvically 20 months post-surgery. Due to her comorbidities, the screw was removed through the hip approach, and the patient passed away six months later from pre-existing health issues.A literature review of 17 reported cases revealed that screw migration often occurs due to improper screw placement, repeated axial loading, and unstable fixation. Prevention strategies emphasize achieving an anatomical reduction, selecting an appropriately sized screw, and proper follow-up to detect complications early. Treatment options include screw removal via open surgery, laparotomy, laparoscopy, or endovascular approaches.In conclusion, medial migration of the lag screw is rare but significant. Preventing this complication requires optimal fracture reduction, precise screw placement, and proper follow-up to avoid severe consequences for the patient.
Keywords: macular hole; microinvasive vitrectomy; platelet-rich plasma; internal limiting membrane; Artery of Percheron; thalamic infarct; bilateral stroke; young adult; vertical gaze palsy; altered consciousness; education; mothers; newborn care; ANC.; cephalic screw; intrapelvic migration; hip fracture; Gamma 3 nail; PFNA nail; surgery complications.